Պղտորագետը և իր ավազանը - Մինասյան, Սիլվա (ԱրՊՀ հրատ․)
Река Пхторагет- Гярак будучи вторым притоком Трту берет начало с западных склонов горы Мрав и имеет большой бассейн. Его притоки Ариклу и Акнаджур – Дагнак сливаются у нового жилого квартала села Чапар. Оба названия этой реки имеют армянское происхождение. В статье дается географическая характеристика реки и приводятся исторические сведения и этимология местностей, расположенных в его бассейне. River Pghtoraget-Gyarak being the second influx of Trtu originates from the western slopes of Mount Mrav and has a large swimming pool. Its tributaries Ariklu and Aknadzhur-Dagnak merge with the new residential area of the village of Chapar. Both names of this river are of Armenian origin. The article provides information with the geographical description of the river, the historical background and etymology areas located in its basin.
Keywords: Արցախ; Ջրային ռեսուրսներ